Weichselian ice dynamics in Jämtland, central Sweden: Lithostratigraphic study of the Köttsjön till deposits - Filbà I Serra,Laura (Dissertations in Geology at Lund University, 2025)
This study provides a comprehensive sedimentological and geochemical analysis of the Late Quaternary Köttsjön sequence in central Sweden. Its aim is to identify the processes and transport mechanisms involved in till formation, and to investigate ice dynamics and sediment provenance. Ultimately, the research contributes to a better understanding of glacial dynamics and palaeoenvironmental evolution in central Scandinavia, particularly the complexity of Middle to Late Weichselian ice-sheet behaviour. The stratigraphic succession consists of six units, including several till beds (the lowermost known as the “old clayey till” or “blue till”) interbedded with sorted sediments. These tills record at least two major glacial advances, which, when correlated with the regional stratigraphy, likely occurred during MIS 4 and MIS 2. These advances are separated by an interstadial period (MIS 3) characterized by meltwater deposits and ice retreat. Clast fabric and lithology analyses reveal shifts in ice flow direction from NW–SE to NE–SW, reflecting changes in the position of the ice divide. Geochemical data support these findings and suggest sediment reworking and varying weathering conditions (particularly within the lower till) highlighting the influence of environmental factors such as soil development.
Keywords: Sedimentological analysis; geochemical analysis; till formation; Weichselian; blue till; clast fabric; lithology analisis; ice flow direction